Awake and fully mobile patients on cardiac extracorporeal life support - Abrams, Darryl; Garan, A. Reshad; Brodie, Daniel (Annals of Cardiothoracic Surgery; Vol 8, No 1 (January 01, 2019): Extracorporeal Life Support in Refractory Heart Failure, 2018)
Early mobilization of critically ill patients is increasingly being recognized as not only safe and feasible, but also as a potential means of optimizing outcomes in the intensive care unit (ICU). With the rapidly expanding use of extracorporeal life support (ECLS) for severe cardiopulmonary failure, there is a growing interest in the application of early mobilization to this patient population, which has been shown to be safe and feasible in select patient populations. However, some patients receiving ECLS support may benefit more than others. For instance, early mobilization may be particularly beneficial in patients awaiting heart or lung transplantation, as maintenance of physical conditioning may be an important component of a patient’s transplant candidacy. The ability to engage critically ill patients in active physical therapy and early mobilization necessarily involves minimization of sedation and is often further facilitated by a strategy that favors endotracheal extubation. Whether an awake, extubated and mobile strategy can be applied in any given patient is often dictated by the severity of the underlying disease and the amount of extracorporeal support required. Additionally, whether this approach is superior to usual care, which patients might benefit or be harmed, and which patient characteristics are most likely to predict success of this strategy, are areas of ongoing investigation.